2021
DOI: 10.35489/bsg-rise-wp_2021/060
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Parental Involvement in Schools: Evidence from Two Randomized Experiments

Abstract: Parental involvement programs aim to strengthen school-home relations with the goal of improving children’s educational outcomes. We examine the effects of a parental involvement program in Mexico, which provides parent associations with grants and information. We separately estimate the effect of the grants from the effect of the information using data from two randomized controlled trials conducted by the government during the rollout of the program. Grants to parent associations did not improve educational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…Unlike the other interventions mentioned in this paragraph, the parent training sessions in Barrera-Osorio et al (2021) did not improve student learning. However, they had the positive effect of reducing disciplinary actions in schools.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Unlike the other interventions mentioned in this paragraph, the parent training sessions in Barrera-Osorio et al (2021) did not improve student learning. However, they had the positive effect of reducing disciplinary actions in schools.…”
mentioning
confidence: 57%
“…Thus, together with the prior analyses of KIAT Guru, this paper contributes to the growing body of research on interventions that aim to improve education service delivery in developing countries by empowering parents and local communities. These include interventions that target parents' awareness of how to improve educational quality (for example, Barrera-Osorio et al [2021] on providing training sessions to parent associations in Mexico); 2 interventions that improve parents' access to information on student and school performance (for example, Andrabi, Das, and Khwaja [2017] on school report cards in Pakistan); and interventions that improve parent-teacher communication (for example, Islam [2019] on parent-teacher meetings to discuss student progress in Bangladesh).…”
mentioning
confidence: 99%
“…While national governments took the initiative in some cases, international development agencies played a major role in the popularization of SBM reforms in LMICs, often making decentralization reforms a precondition for financial aid (Bjork, 2006). Barrera‐Osorio et al (2009) reported that SBM projects constituted about 10% of all World Bank education projects and 18% of its total education financing between 2000 and 2006. Consequently, Caldwell (2005, p. 3) observed that “school‐based management has been evident in policy and practice for more than three decades to the point that there are now few nations that have not moved down this track.”…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there had been previous models of SBM in which control over school management was awarded solely to school principals and/or teachers, most SBM reforms in LMICs prioritized the involvement of parents and the local community. Barrera‐Osorio et al (2009, p. 17) noted that “SBM in almost all of its manifestations involves community members in school decision making.” The rationale for this was to bypass higher levels of educational administration by creating a “short route” to accountability (World Bank, 2003): one in which parents, who have a large stake in improving the quality of the school that their children attend, were empowered to have a say in school management. In this respect, SBM reforms were seen as part of a wider movement to improve public services by strengthening community‐based accountability mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation